Lysogenic Conversion for Multiple Characters in a Strain of Staphylococcus aureus - Duval-Iflah, Yvonne (1977)
Lysogenization of nonlysogenic strains of Staphylococcus aureus was performed with two different bacteriophages, LS1 and LS2, that were unable to plaque on any of the strains of S. aureus tested. Infection of recipient strains was achieved when protoplasts were inoculated with LS1 or LS2 or when bacterial cultures were simultaneously inoculated with a virulent phage together with LS1 or LS2. Lysogenization was demonstrated by changes in phenotypic characters of the host strain and by liberation of bacteriophages from the modified strains as shown by electron microscopic examination. The lysogenic strains differed from the host strains by the following characters: they were coagulase, deoxyribonuclease, and lipase negative; they were untypable by the basic set of phages; they did not ferment mannitol under anaerobic conditions; and they produced only l-(+)-lactic acid by glucose fermentation. Their cell walls contained less glycine and concomitantly more serine than those of the host strains. Furthermore, they were devoid of protein A. Conversely, some antigenic factors as well as the presence of ribitol in the cell wall teichoic acid, indicated a parental relationship between the host strains and the derived lysogenic ones. Phages LS1 and LS2 could be excluded from the lysogenic strains by invading phages, and the revertant nonlysogenic strains recovered all of the characteristics of the initial host strains. It was thus concluded that the phenomenon described was due to lysogenic conversion. The origin of phages LS1 and LS2 is discussed.